Advances in 3D Bioprinting for Corneal Regeneration - Juan Hernández; Nicolás Santos; Manuel Ahumada (Gels, 2025)
Worldwide, millions of people suffer from visual impairments, ranging from partial to total blindness, with far-reaching consequences on personal, societal, and governmental levels. Corneal-related issues are among the leading causes of blindness, with corneal transplantation (keratoplasty) being the primary treatment. However, the demand for donor tissues far exceeds supply. The rise of printing technologies marks a revolution in tissue engineering, with 3D bioprinting at the forefront of developing innovative tissue repair and replacement solutions. The cornea emerges as an ideal candidate for this technology due to its distinct layers (epithelium, stroma, and endothelium). From a materials engineering standpoint, these layers resemble a hydrogel structure that facilitates fabrication. This review explores advancements in 3D bioprinting, focusing on the methodologies developed for corneal tissue engineering. It highlights design and construction aspects, including biomechanical and biocompatibility properties essential for creating synthetic implants and corneal scaffolds through bioprinting. Additionally, the review discusses the challenges and opportunities that could further drive innovation in tissue engineering.